Hellenic references in Edgar Allan Poe’s critique on contemporary society - Tsokanos, Dimitrios (International Journal of English Studies, 2016)
Edgar Allan Poe’s bicentenary triggered new translations and research on his life and works. Studies have been conducted by several noteworthy scholars such as Silverman (1991) and Peeples (1998 and 2004) indicating that the selected tales in this essay are Poe’s political message to the society of his time. The presence of Latin and Hellenic phrases and names in Poe’s critique has been indicated in the past. However, despite the existence of numerous analyses with respect to the Latin motifs in Poe’s narratives, even in Lois Vines’ Poe Abroad (1999) there has been no research dedicated to the apparent presence of Hellenic references in Poe’s works. Moreover, a methodic study devoted to the presence of the Hellenic domain in Poe’s storytelling has never been undertaken. Presenting promismcging evidence for an extensive study, I aim to delve into these references and identify the reasons why Poe turned to Greece as a source of inspiration.